Success factors of transformative learning for sustainable development - Tobias Joachim Schnitzler (Südwind-Verlag, 2020)
The human capacity to learn through formal or informal education is considered a key resource for achieving sustainable development on a global scale. Accordingly, the UN-Agenda 2030 and the Sustainable Development Goals refer to education and its transformative power by integrating it both as a cross-cutting issue and as target 4.7. However, there are many different practical, pedagogical and scientific approaches to what and, above all, how something is to be learned and how it shall contribute to change. The spectrum is broad and ranges from traditional educational concepts, education for sustainable development, global citizenship education to concepts of transgressive learning. While some of these concepts seek to extend traditional approaches to education by simply adding specific learning content, others are concerned with far-reaching transformations at individual (learners), collective (organisation) and, to varying degrees, structural (society) level. This is the starting point of Tobias Schnitzler's dissertation, which focuses on the collective level and aims to investigate success factors of transformative learning for sustainable development in organisations. In his cumulative thesis, Tobias Schnitzler first analyses at a theoretical level the differences and possible bridges between Education for Sustainable Development and transformative learning. He concludes that critical reflection, participation and social engagement must be taken into account, if Education for Sustainable Development is to be transformative. The second and third sections contain empirical studies. Learning in start-ups and NGOs is examined with the help of innovative WeQ tests that focus on the collective "We". On the other hand, Schnitzler analyses the possibilities and limits of creating a sustainable partnership between UN organisations that are cooperating in the context of the SDGs. Success factors for transformative learning within organisations are identified from these empirical studies. Tobias Schnitzler's work offers a valuable insight into the dynamics of learning within organisations on a broad conceptual basis of transformative learning theories. Beyond the mere assumption of the effectiveness of learning, it thus makes an important contribution to understanding concrete prerequisites and conditions for making learning transformative and meaningful for sustainable development.
Keywords: 320